Análisis del efecto inmediato y diferido de la orientación al mercado sobre los resultados organizacionales. Un estudio longitudinal - Lourdes Cauzo Bottala; Francisco José Cossío Silva (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2012)
– The aim of this work focuses on analyzing the effect, both immediate and delayed, of Market Orientation (MO) on organizational outcomes. A longitudinal study has been done over a time horizon of 3 years in the Spanish financial sector. Regarding the methodology, we have developed a qualitative method to measure the degree of OM of the entities considered, through a content analysis. After obtaining an indicator of this analysis, we applied a quantitative methodology of structural equation modeling for testing hypotheses of the proposed model. From the results, we highlight, first, banks that implement a MO approach are likely to maintain that approach in subsequent periods. Secondly, immediate effects of MO on results were not found. And finally, MO does not record deferred effects on the considered indicators of profitability.
Keywords: M1; M3; O3; 650; market orientation; performance; longitudinal analysis; qualitative analysis; content analysis